Implementasi Pendidikan Karakter Dalam Muatan Lokal Pembelajaran Bahasa Indonesia Pada Era Society 5.0 - Muhammad Irgi Fahrezi; Jessica Nabila; Ichsan Fauzi Rahman (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2023)
Era Society 5.0. which is characterized by the integration of high technology and artificial intelligence. Creating new challenges and opportunities in the world of education. Rapid social changes, global demands, and technological developments are factors that influence the transformation of character education and Indonesian language learning. Character education is the process of forming students’ values, attitudes and morals as well as the formation of quality character. Qualitative methods are used to describe and explain phenomena or events in detail and carefully. The use of smart applications, data analysis, and digital platforms enriches students’ learning experiences, fosters creativity, and increases their understanding of Indonesian as an important medium of communication. In implementing character education and Indonesian language learning in the Society 5.0 era. Qualitative approaches are effective tools for understanding complex and dynamic contexts. Through content analysis, research can identify the weaknesses and strengths of the existing curriculum and provide recommendations for improvement. The results of this research can make a significant contribution to the design of more effective educational strategies and relevant to the needs of modern society.